Determinaciòn de staphyloccus aureus - Remachi Defaz, Katherine Milena (2017)
The aim of this research was to determine the presence of Stafilococcus aureus in the patients of the "SAN VICENTE DE PAÚL" Basic Hospital in Pasaje, with diabetic foot ulcer, being the consequence of uncontrolled diabetes mellitus together with microbiological growth (bacteria, parasites , Fungi), complicating this picture. By means of bacterial identification microbiological tests, along with the Wagner classification that measures the depth of the wound: grade 0: with absence of ulcer, foot at risk (deformity, hyperkeratosis), grade 1: superficial ulcer, grade 2: deep ulcer Includes tendon and joint capsule, grade 3: deep ulcer with abscess, osteomyelitis or joint sepsis, grade 4: localized gangrene (forefoot or heel), grade 5: extensive gangrene. The demographic characteristics of the patients were determined, the identification of the bacteria in the laboratory, determining the incidence of Staphylococcus aureus in diabetic foot ulcers and preventing them from reaching a chronic infection. Through the experimental, observational, qualitative study, surveys were conducted to determine the incidence of Stafilococcus aureus, according to: age, sex, surgical cleaning, medical control, previous amputation feeding and hygiene habits. The sample collection was carried out at the institution, afterwards conservation and transportation. Microbiological laboratory was used: qualitative techniques, macroscopy, microscopy, Gram staining, basic biochemistry, coagulase test, Kirby-Bauer antibiogram, and quantitative techniques; Colony count inoculation (CFU), for bacterial identification and appropriate treatment. It was determined that most of the samples present Stafilococcus aureus with 48%, followed by Escherichia coli with 17% and in a lower percentage the Pseudomona aeruginosa with 5%. Patients were classified to analyze the incidence according to age group, which the highest percentage is found in individuals aged 50-64 years with 35%; Followed with patients aged 65 years and 33% and 2% for patients 20 to 49 years. According to the surveys applied to the patients of the Hospital San Vicente de Paúl, it was determined that the acquired infection is due to the poor hygiene habit, 55% of the respondents said that 38% indicated that they have a poor hygiene habit, have not Performed culture, antibiogram, before instituting a treatment, and few have been amputated, surgical cleaning is performed by the trained professional of this institution. Staphylococcus aureus is considered the main causal agent of infection in patients with diabetic foot, both in the community and in the hospital setting. Since it is responsible for a wide range of diseases such as superficial skin infections to soft tissue and osteo-articular infections such as: deep abscesses, cellulitis, infection of surgical wounds, osteomyelitis, etc., and was the predominantly isolated microorganism, The bibliographic review. This analytical investigation showed that the causal agent with the highest incidence in patients with diabetic foot at San Vicente de Paul Hospital, Canton Pasaje, El Oro Province, is Stafilococcus aureus, in diabetic foot ulcers and in most cases The male sex and the age group of 50-64 years.